Effect Games Gobak Sodor and Hopscotch on Power Limb Muscles: Male Students Class III Islamic Primary School District Gurah Kediri Regency 2017/2018 - Utomo, Rusidi Priyo (PINUS: Jurnal Penelitian Inovasi Pembelajaran, 2019)
This research is motivated by observations and experiences of researchers in taking the jump results without prefix carried out by male students of grade 3 in Islamic elementary schools. Based on the results of the jump, the value is far from the average jump ability of male students in grade 3 because the learning method is not maximal. The problem in this study is Is there an influence of gobak sodor and crank play on the explosive power of leg muscles? Are there differences in the results of leg muscle explosive power using the game Gobaksodor and Crank? This research is quantitative research because the results of the research are in the form of numbers. Research with Quasi Pre-Experiment Design using pretest and posttest design, the research instrument used observation on the Standing long jump test, and the subject of third-grade male students of Islamic Primary School with 81 students held for 1 month. From the results of the study, it was found that the average yield of the gobak sodor game pretest was 125 cm and the crank game was 124 cm. After being given treatment, the posttest results of the game of gobak sodor were 142 cm and the game of cranks was 141 cm, from the results it was obtained the difference in results from the game gobak sodor and engklek of 17 cm. And tested using a simultaneous test (F test) obtained a significance value of 482,674> 2, 72 F table which shows the influence of gobaks odor and crank play on the explosive power of limb muscles of third grade students of Islamic Elementary School, from the partial test (t-test) presented the result is 11,692> 1,66515 which shows the gobak sodor and crank game has its own influence. To find out the difference in results, an independent sample test was carried out so that the results obtained for t count for the independent variable were 0, 342> 0, 05. It was concluded that there were no differences in results using the game gobak sodor and crank. From the test results, it can be concluded that there are effects of sodor and crankshaft play on leg muscle explosive power and there is no difference in the results of leg muscle explosive power using gobak sodor and crank games in third grade male students of Islamic Elementary School in Gurah District, Kediri District 2017/2018 Academic Year.